REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN MIND MAPPING TENTANG USAHA DI SMA - Indri Khoirunisa; Stepanus Sahala Sitompul; Syukran Mursyid (Universitas Tanjungpura, 2020)
Abstract This study aimed to asses the effectiveness of Guided Inquiry Learning Model with Mind Mapping to remediate student’s misconception on ‘work’ for grade X IPA student of SMA Negeri 3 Pontianak.. The method used in this research was preexperimental method with the one-group pretest-posttest design. Samples of study were purposive sampling and selected base on Physics teacher’s recommendation. The instrument of research included 10 questions of diagnostic test. The average range of students misconception in pre test was 82,94% and in post test was 30% . The average range decreased 64,36% after the treatment. Based on McNemar test, overall students experienced significant misconception with value of χ2 count (82,51) > χ 2 table (3,84), df=1 and α = 5%. The effectiveness of Guided Inquiry Learning Model with Mind Mapping to remediate student’s misconception about ‘work’ that used to reduce the misconcepted students through DQM of 64,37% which included in medium category. Therefore, teachers suggested to used Guided Inquiry Learning Model as alternative learning technique in order to straighten out student misconception in the material ‘work’. Keywords: Guided Inquiry, Mind Mapping, Remediation.